Porous carbon nanoparticles dispersed nematic liquid crystal: influence of the particle size on electro-optical and dielectric parameters. Issue 7 (15th July 2022) - Pathak, Govind; Hegde, Rekha S.; Punjalkatte, Supriya S; Rujiralai, Thitima; Hegde, Gurumurthy; Prasad, Veena
ABSTRACT: Porous carbon nanoparticles (PCNPs) of four different sizes ( 180 nm, 51 nm, 41 and 25 nm) were dispersed into a nematic liquid crystal (NLC) in 0.25 wt% concentration. PCNPs were derived from biowaste materials and pyrolysed at elevated temperatures to get the porous structure. Polarising optical microscopic observations were carried out in dark and bright states on both the pure NLC as well as NLC-PCNPs composites. Homogeneous alignment was well maintained in all the composites except the one with the highest sized ( 180 nm) PCNPs. Birefringence, relative permittivity and dielectric anisotropy, increases as the size of the PCNPs is decreased in the composites. The threshold voltage was also found to decrease with the decrease in the size of the PCNPs. Such investigations may be useful for the fabrication of display devices such as flat panel displays (FPDs) and phase shifters. Graphical Abstract: uf0001